"Ebola kills generations": Qualitative discussions with Liberian healthcare providers. (February 2017) - Bell, Sue Anne; Munro-Kramer, Michelle L.; Eisenberg, Marisa C.; Williams, Garfee; Amarah, Patricia; Lori, Jody R.
Abstract: Objective: the purpose of this study was to explore healthcare providers' perceptions and reactions to the Ebola Virus Disease (EVD) epidemic. Design: a descriptive, qualitative study design was employed. Focus groups were conducted with Liberian healthcare providers who participated in care of patients with EVD. Setting: the study was conducted in Bong County, Liberia (population: 333, 000), which was severely affected, with over 650 reported cases and close to 200 deaths by the end of 2015. Participants: the total sample of 58 participants, included 11 nurses, ten traditional birth attendants (TBAs), four midwives, 28 general community health volunteers, three physician assistants, one community member and one pharmacy dispenser. Measurements and findings: five core themes related to changes in healthcare practices and interactions since the EVD outbreak were identified based on the results of the focus groups; fear, stigma, resource constraints, lack of knowledge and training, and shifting cultural practices. Key conclusions: this work represents a preliminary understanding of Liberian healthcare workers reactions to the EVD epidemic, and highlights the significant issues they faced as they attempted to care for patients and protect themselves. Implications for practice: while the EVD epidemic has been declared over, preparedness activities for future disease outbreaks must continue. This study can inform future healthcare policy initiatives as well as preparedness activities targeted towards healthcare workers in low resource settings.